Language’s Inception and Evolution its Present and Future Prospects - Hussain Jami, Mustansar; Ul Hassan, Mehmood (sourcecoder, 2022)
Man has made great progress from the first day to the present. In all this development, language played very important role. The human language spread widly and human life was accelerated by the intervention of the machine. The scientific age broke all the records and took the pace of development beyond the speed of sound. The scientific age filled the human language with endless terms and techniques. The use of human language is declining, which will eventually become extinct and will be limited to the private affairs of life. The discussions that are going on today about code-mixing and code-switching in language are just the beginning of a new international language.